The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.2193/0022-541x(2006)70[1070:sonyeb]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Northern Yellowstone Elk by Gray Wolves and Hunters

Abstract: We compared selection of northern Yellowstone elk (Cervus elaphus) by hunters in the Gardiner Late Hunt and northern Yellowstone wolves (Canis lupus) with regard to sex, age, and impacts to recruitment. We compared harvest data from 1996–2001 with wolf‐killed elk data from 1995–2001. We assessed the effects of hunting and wolf predation on reproductive female elk by constructing a life table and calculating reproductive values for females in the northern Yellowstone herd. We devised an index of total reproduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
116
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(124 citation statements)
references
References 30 publications
8
116
0
Order By: Relevance
“…We found a weak negative relationship between age and survival, which was consistent with age-specific variation in survival found in other ungulate populations (Loison et al 1999;Gaillard et al 2000;Festa-Bianchet et al 2003). A negative relationship between survival and age in the Fort Riley population could be due to hunters avoiding harvesting a calf or yearling, and thereby increasing the mortality risk for adult female elk in older age-classes (Wright et al 2006). The average age at harvest for female elk at Fort Riley ( x x = 6.9 y) was within what has been defined as the prime-age life stage for elk (2-9 y; Raithel et al 2007), and is similar to the average age of elk harvested from a population in Idaho ( x x = 7.3 y; Husseman et al 2003).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We found a weak negative relationship between age and survival, which was consistent with age-specific variation in survival found in other ungulate populations (Loison et al 1999;Gaillard et al 2000;Festa-Bianchet et al 2003). A negative relationship between survival and age in the Fort Riley population could be due to hunters avoiding harvesting a calf or yearling, and thereby increasing the mortality risk for adult female elk in older age-classes (Wright et al 2006). The average age at harvest for female elk at Fort Riley ( x x = 6.9 y) was within what has been defined as the prime-age life stage for elk (2-9 y; Raithel et al 2007), and is similar to the average age of elk harvested from a population in Idaho ( x x = 7.3 y; Husseman et al 2003).…”
Section: Discussionsupporting
confidence: 86%
“…As the primary source of mortality, hunting is expected to directly influence adult survival rates, which may subsequently influence the overall rate of population growth (l). Harvest may have a particularly strong influence on population dynamics if prime-age classes are selectively harvested (Wright et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Associated trophic cascades have been documented, including recovery of riparian vegetation (Beyer et al 2007) and aspen (Ripple and Beschta 2007). The greater reproductive impact of cow elk hunting relative to wolf predation (Wright et al 2006) suggested adjusting hunting pressure was a more powerful management tool than predation for regulating elk population size. Whether coyotes on our study area are capable of filling a similar niche to wolves in Yellowstone is doubtful.…”
Section: Discussionmentioning
confidence: 99%
“…The elaborate stotting that prey such as Thomson's gazelles, Gazella thomsoni, perform at the beginning of a predator attack suggests that the predators are capable of detecting slight differences in the motor performance of prey (FitzGibbon & Fanshawe 1988). It is also well known that predators efficiently identify weak, injured or sick prey (Mills, 1990;Quinn and Cresswell, 2004;Martin et al, 2006;Wright et al, 2006). In summary, natural selection on predators has probably enhanced animals' ability to detect subtle differences in the motor performance of potential prey.…”
Section: Motor Performance As Skillmentioning
confidence: 99%